Megestrol acetate for cachexia–anorexia syndrome. A systematic review. Issue 3 (14th March 2018) - Ruiz‐García, Vicente; López‐Briz, Eduardo; Carbonell‐Sanchis, Rafael; Bort‐Martí, Sylvia; Gonzálvez‐Perales, José Luis
Abstract: In 1993, megestrol acetate (MA) was approved by the US Food and Drug Administration for the treatment of anorexia, cachexia, or unexplained weight loss in patients with acquired immunodeficiency syndrome. The mechanism by which MA increases appetite is unknown, and its effectiveness for anorexia and cachexia in neoplastic, elderly, and acquired immunodeficiency syndrome patients is under investigation. This is an updated version of a Cochrane systematic review first published in 2005 and later updated in 2013 entitled 'Megestrol acetate for the treatment of anorexia–cachexia syndrome'. MA vs. placebo: in studies where MA was compared with placebo, the overall results showed that MA patients gained weight (mean difference, MD 2.25 kg, 95% CI [1.19, 3.3]) but did not gain quality of life (QOL) (standarized mean difference, SMD 0.5, 95% CI [−0.13, 1.13]), with more adverse events (relative risk, RR 1.46, 95% CI [1.05, 2.04]), but no difference in deaths (RR 1.26, 95% CI [0.70, 2.27]). MA vs. no treatment: MA patients gained weight (MD 1.45 kg, 95% CI [0.15, 2.75]) but did not gain QOL (standardized mean difference 3.89 95% CI [−14, 6.28]). There was no increase in adverse events (RR 0.90, 95% CI [0.39, 2.08]) or deaths (RR 1.01, 95% CI [0.42, 2.45]). MA vs. active drugs: MA patients gained weight (MD 2.5 kg, 95% CI [0.37, 4.64]) but did not gain QOL (MD 0.20 95% CI [−0.02, 0.43]) and did not report an increase in adverse events (RR 1.05 95% CI [0.95, 1.16]) or in deaths (RR 1.53, 95% CI [1.02, 2.29]) Different doses of MA: in studies where lower doses of MA were compared with higher doses of MA, we did not find differences either in weight gain (MD −0.94 kg, 95% CI [−3.33, 1.45]), QOL (MD 0.31 95% CI [−0.19, 0.81]), or adverse events (RR 1.34, 95% CI [0.65, 2.76]). Thus, we cannot reach a conclusion for an optimal dose of MA.